Circular economy-based multi-objective decentralized controller for activated sludge wastewater treatment plant - Subbian, Sutha; Natarajan, Pappa; Murugan, Chitra (Frontiers in Chemical Engineering, 2023)
Water scarcity and water pollution are the two major issues in India. Circular economy-based wastewater treatment technology provides most sustainable solutions for solving the above issues. In this paper, a novel Multi-Objective Decentralized Controller (MODC) is proposed for benchmark Multi-Input Multi-Output (MIMO) activated sludge waste water treatment plant to achieve maximum effluent quality with minimum cost. Waste Water Treatment Plant (WWTP) with conventional control scheme consumes more energy to achieve the desired effluent quality. In this study, MIMO model is developed for Activated Sludge Process (ASP) from physics based model and Relative Gain Array (RGA) analysis is carried out to determine the interaction between the loops to identify suitable control scheme for MIMO process. In addition, multi-objective decentralized control problem is formulated to achieve the conflicting multi-objectives of improving effluent quality and minimizing operational cost by efficient usage of energy. The desired quality and cost reduction are ensured by Integral Square Error (ISE) and Control Effort (CE). The Multi-Objective control problem is successfully solved by Multi-Objective Evolutionary Algorithm (MOEA) namely Non-dominated Sorting Genetic Algorithm (NSGA)-II. NSGA-II provides number of optimal solutions in the pareto front. In order to demonstrate the feasibility of the proposed controller, three optimal solutions are selected from the pareto optimal front and their closed-loop performances are evaluated qualitatively as well as quantitatively for both servo and regulatory operations. The improving the quality of effluent enhances the active sludge production which in turn increase the methane production in the anerobic digester.